Reformasi Tata Kelola Transisi di Bidang Pelayanan Perizinan: Studi kasus Penerbitan Layanan Perizinan Usaha (IMB) di Kabupaten Badung - Ni Made Dwi Widari (STISIP Margarana, 2026)
This study explores the dynamics of governance reform in the context of institutional transition of business licensing services in Badung Regency, Bali. The transformation from the Integrated Licensing Service Agency (BPPT) to the Investment and One-Stop Integrated Service Agency (DPMPTSP), and then to the Public Service Mall (MPP) model, reflects the local government's systematic efforts to respond to demands for transparency, efficiency, and accessibility of public services in the digital era. Badung Regency, as one of Indonesia's leading tourism destinations with high economic dynamics, faces dual pressures: on the one hand, it must facilitate rapid investment and business growth, and on the other hand, it must ensure accountable licensing governance and protect the interests of local communities. This context makes the Badung case study relevant and strategic for understanding how governance reform is implemented in the complex reality of local governance. The purpose of this study is to analyze the process, challenges, and impacts of transitional governance reforms on business licensing services in Badung Regency for the 2017-2024 period. This study specifically examines changes in institutional structures that may affect the quality of public services, the extent to which digitalization of the licensing process has changed patterns of interaction between the government and business actors, and how these practices are impacted.good governance applied in the context of organizational transition involving changes in systems, work culture, and human resource capacity. The research method used was descriptive qualitative with a case study approach. Data were collected through in-depth interviews with key stakeholders, including the heads of departments and staff of the Badung Regency DPMPTSP, business actors from various sectors (tourism, trade, services), and the general public who had previously processed business permits. Direct observations were conducted at the service offices to understand the dynamics of daily operations, interaction patterns between officers and applicants, and the effectiveness of the system used. Document analysis was conducted on regional regulations, standard operating procedures, annual performance reports for the 2017-2024 period, and licensing statistics, including the number of permits processed, completion times, public satisfaction levels, and complaints received. Data triangulation was conducted to ensure the validity of the findings by comparing perspectives from various sources and data collection methods. This research's contribution lies in its in-depth elaboration of the dynamics of governance reform within the context of organizational transition involving simultaneous changes in structure, systems, technology, and culture. Unlike previous studies that tend to focus on the technical aspects of digitalization or administrative performance evaluation, this research adopts a holistic perspective that considers the institutional, socio-technical, and political-economic dimensions of licensing reform. The research findings provide practical insights for other local governments undertaking or planning similar reforms, particularly regarding change management strategies, the importance of early stakeholder involvement, and the need to balance procedural standardization with flexibility to accommodate specific local needs.